The impact of exposure to mass media campaigns and social support on levels and trends of HIV-related stigma and discrimination in Nigeria: Tools for enhancing effective HIV prevention programmes - Fakolade, R.; Adebayo, S.B.; Anyanti, J.; Ankomah, A. (My University, 2010)
People living with HIV and AIDS (PLWHAs) often face stigma and discrimination, especially in developing countries. HIV-related stigma is expressed through social ostracism, personal rejection, direct and indirect discrimination, and denial from families and friends. Consequently, it is associated with reduced adoption of preventive and care behaviours, including condom use, seeking for HIV test and care-seeking behaviour subsequent to diagnosis. Ignorance about the epidemiology of the disease on modes of transmission and prevention aggravates HIV-related stigma in Nigeria. Behaviour change communication activities through mass media have been shown to be an effective approach in improving people's knowledge about the disease. This paper monitors trends in the level of accepting attitudes towards PLWHAs in Nigeria between 2003 and 2007. It also evaluates the impact of exposure to mass media and social support on the levels of accepting attitudes towards PLWHAs. A significant and positive trend was evident between 2003 and 2007 (p<0.0001). Furthermore, exposure to mass media communications on HIV and AIDS issues and social support were significantly related to the reduced stigma and discrimination against PLWHAs (p<0.0001).